2006
DOI: 10.1037/1040-3590.18.4.382
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and construct validity of the psychopathy checklist-revised for Latino, European American, and African American male inmates.

Abstract: The utility of the psychopathy construct in predicting laboratory deficits, criminal behavior, response to intervention, and recidivism has been well documented in European American populations. However, less is known about the manifestation and correlates of psychopathy in Latino and African American populations. The present study examined the reliability and construct validity of the Psychopathy Checklist - Revised (PCL-R; R. D. Hare, 2003) in 83 Latino inmates compared with matched samples of African Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 59 publications
2
39
0
1
Order By: Relevance
“…A number of prior studies have focused on investigating potential differences in alcohol use and psychopathic features across ethnic groups (e.g., Chartier & Caetano, 2010; Grant, Vergés, Jackson, Trull, Sher, & Bucholz, 2012; Sullivan, Abramowitz, Lopez & Kosson, 2006). Therefore, a supplemental analysis was conducted that examined multi-group invariance in the final LCM-SR model across African-American, Caucasian, and Hispanic ethnic groups.…”
Section: Resultsmentioning
confidence: 99%
“…A number of prior studies have focused on investigating potential differences in alcohol use and psychopathic features across ethnic groups (e.g., Chartier & Caetano, 2010; Grant, Vergés, Jackson, Trull, Sher, & Bucholz, 2012; Sullivan, Abramowitz, Lopez & Kosson, 2006). Therefore, a supplemental analysis was conducted that examined multi-group invariance in the final LCM-SR model across African-American, Caucasian, and Hispanic ethnic groups.…”
Section: Resultsmentioning
confidence: 99%
“…Sullivan, Abramowitz, Lopez, and Kosson (2006) demonstrated structural consistency and construct validity of PCL-R psychopathy across European American, Latino, and African American subcultures in North America. Research in the United Kingdom has revealed configural and metric invariance of PCL-R ratings across prisoner nationalities (Cooke et al, 2005), and good cross-national reliability of PCL-R scores has been established between Scottish and Canadian assessors (Cooke et al, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…There is also initial evidence that psychopathy can be adequately measured by the PCL-R in Latino Americans (LA) (Sullivan, Abramowitz, Lopez, & Kosson, 2006). However, several studies have reported differences between EA and AA individuals on laboratory measures of mechanisms thought to underlie psychopathy (Doninger & Kosson, 2001;Lorenz & Newman, 2002), and it has been proposed that ethnicity should be routinely considered in psychopathy research, particularly with regards to criminality (Walsh et al, 2004).…”
Section: Ethnicitymentioning
confidence: 98%